Computer Vision and Graphics International Conference, ICCVG 2004, Warsaw, Poland, September 2004, Proceedings - Wojciechowski, K.; Smolka, B.; Palus, H.; Kozera, R.S.; Skarbek, W.; Noakes, L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
As the speed, capabilities, and economic advantages of modern digital devices c- tinue to grow, the need for ef?cient information processing, especially in computer - sion and graphics, dramatically increases. Growth in these ?elds stimulated by eme- ing applications has been both in concepts and techniques. New ideas, concepts and techniques are developed, presented, discussed and evaluated, subsequently expanded or abandoned. Such processes take place in different forms in various ?elds of the c- puter science and technology. The objectives of the ICCVG are: presentation of current research topics and d- cussions leading to the integration of the community engaged in machine vision and computer graphics, carrying out and supporting research in the ?eld and ?nally pro- tion of new applications. The ICCVG is a continuation of the former International Conference on Computer Graphics and Image Processing called GKPO, held in Poland every second year in May since 1990, organized by the Institute of Computer Science of the Polish Academy of Sciences, Warsaw and chaired by the Editor of the International Journal of Machine Graphics and Vision, Prof. Wojciech S. Mokrzycki.
Keywords: Computer science; Computer graphics; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Electronic books